Sternum drop during trip recovery differs between the laboratory and real world – An exploratory pilot study - Youngjae Lee; Neil B. Alexander; Christopher T. Franck; Michael L. Madigan (PLoS ONE, 2025)
The goal of this exploratory study was to compare sternum drop—the decrease in sternum height during an attempt to recover balance after tripping—between lab-induced trips and naturally occurring real-world trips. Twenty community-dwelling adults 71.8 (4.6) years old used three inertial measurement units (IMUs) and a wrist-worn voice recorder daily for three weeks to capture sternum drop during any naturally-occurring real-world trips. Participants then completed a single laboratory testing session during which they were intentionally exposed to two lab-induced trips while wearing the same IMUs to also evaluate sternum drop. All real-world trips resulted in recoveries while only 12 of the 22 lab-induced trips resulted in recoveries (the remaining 10 were falls). When including all lab-induced trips, sternum drop after real-world trips was 8.8 cm smaller (p < 0.001), exhibited less variance (p < 0.001), and was not associated with lab-induced trips (R2 = 0.005; p = 0.757). When only including lab-induced trips that resulted in recoveries, sternum drop after real-world trips did not differ from the lab (p = 0.163), exhibited less variance (p < 0.001) and was not associated with lab-induced trips (R2 = 0.006; p = 0.766). These results were likely dependent upon 1) our lab protocol that required participants to walk at a gait speed that was likely faster than typical gait speed in the real-world, and 2) the aggressive lab tripping obstacle height of 8.6 cm was likely taller than at least some real-world trips. While reducing gait speed and obstacle height in future laboratory studies may improve agreement with real-world trips, this would lower the physical demands during recovery and may not be as effective at revealing factors contributing to falls. Nevertheless, additional research appears warranted to clarify the linkage between lab and real-world trips. To our knowledge, this is the first study comparing tripping kinematics between the lab and real world.